THE GUARANTEED ANNUAL WAGE AND ACCOUNTING FOR DECISION MAKING. - Schindler, James S. (The Accounting Review, 1959)
Abstract The article focuses on the guaranteed annual wage and accounting for decision making. In recent years, much attention in the U.S. has been centered on plans to cope with unstable incomes through the device of "guaranteed wages." On the one hand, the state governments have instituted plans of unemployment compensation, which might be referred to as a type of guaranteed wage. On the other hand, the guarantee of eight hours of pay if the employee is called in for a shift, regardless of the actual number of hours worked under eight hours, has also been referred to as a guaranteed wage. This article is limited to a discussion of the guaranteed annual wage and approximations to it included among the supplemental unemployment benefit plans. The term "guaranteed annual wage," involves two main ideas. First, it is a method of payment; the emphasis generally laid on the hourly rate is shifted to the annual rate of pay. Secondly, it implies the idea of a minimum wage, which is guaranteed to the employee by the firm.